PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL PEMODERASI (Studi Pada Karyawan CV Batik Wahyu Kencana Pekalongan) - Adipradana, Mahaputra; Andriyani, Andriyani (Faculty of Economics and Business Diponegoro University, 2021)
This study aims to analyze the effect of work discipline and work motivation on employee performance with job satisfaction as a moderating variable. This research consists of two independent variables, one dependent variable, and one moderating variable. The independent variables in this study are work discipline and work motivation. The dependent variable in this study is employee performance. The moderating variable in this study is job satisfaction. The population in this study were all employees of the CV Batik Wahyu Kencana company in Pekalongan City. The study used a population of 85 respondents. The data collection technique is done by using a questionnaire. Analysis of research data using Moderated Regression Analysis (MRA). The results of this study indicate that work discipline on employee performance has a positive and significant effect. Work motivation on employee performance has a positive and significant effect, then job satisfaction can moderate work discipline which has a positive and significant effect on employee performance. Job satisfaction can also moderate work motivation which has a positive and significant effect on employee performance.